Percutaneous microwave ablation vs radiofrequency ablation in the treatment of hepatocellular carcinoma - Poulou, Loukia S (World J Hepatol, 2015)
Hepatocellular cancer ranks fifth among cancers and is related to chronic viral hepatitis, alcohol abuse, steatohepatitis and liver autoimmunity. Surgical resection and orthotopic liver transplantation have curative potential, but fewer than 20% of patients are suitable candidates. Interventional treatments are offered to the vast majority of patients. Radiofrequency (RFA) and microwave ablation (MWA) are among the therapeutic modalities, with similar indications which include the presence of up to three lesions, smaller than 3 cm in size, and the absence of extrahepatic disease. The therapeutic effect of both methods relies on thermal injury, but MWA uses an electromagnetic field as opposed to electrical current used in RFA. Unlike MWA, the effect of RFA is partially limited by the heat-sink effect and increased impedance of the ablated tissue. Compared with RFA, MWA attains a more predictable ablation zone, permits simultaneous treatment of multiple lesions, and achieves larger coagulation volumes in a shorter procedural time. Major complications of both methods are comparable and infrequent (approximately 2%-3%), and they include haemorrhage, infection/abscess, visceral organ injury, liver failure, and pneumothorax. RFA may incur the additional complication of skin burns. Nevertheless, there is no compelling evidence for differences in clinical outcomes, including local recurrence rates and survival.